(untitled) (Student Conference Proceedings, 2025)
Nature exposures can improve psychological wellbeing (PW), but the underlying mechanisms still remain unclear. To address this issue, this pilot study investigated the effects of a 15-minute nature walk compared to an urban walk on PW, assessed through self-reported affect (PANAS), state anxiety (STAI-S), trait anxiety (STAI-T), flow experience as well as awe and gratitude sensation. Environmental parameters and salivary cortisol levels were also measured. Participants (N = 50) followed a standardized study protocol. While no significant differences between the groups were observed, descriptive trends suggested greater improvements in PW in the nature condition. Additionally, participants reported higher scores for awe and gratitude and flow, highlighting the potential role of suchlike experiential states in mediating the benefits of nature exposure. These findings underscore the need for further research investigating the complex interplay between environmental conditions and emotional states.